Anatomical variations of the saphenous and descending genicular artery perforators: Cadaveric study and clinical implications for vascular flaps - Kanit Sananpanich (2018)
BACKGROUND:: With increasing use of free vascular flaps of the saphenous artery and descending genicular artery, the authors investigated the anatomical variations in cadavers. METHODS:: Thirty-one fresh cadaveric thighs were studied by anatomical dissection. The perforators and their source arteries were skeletonized along their courses to the superficial femoral artery and measured. The perforators' nomenclature and abbreviations were modified from the Gent consensus. The skin and bone perforators were evaluated for their role in skin, bone, and osteocutaneous flaps. RESULTS:: The descending genicular artery was noted in 27 thighs (87 percent) and gave rise to at least one skin perforator that could be used to develop an osteocutaneous flap. The chimeric pedicle length increased and the chimeric arm length decreased, as the descending genicular artery skin perforators were more distally located. The saphenous artery was noted in all 31 thighs, and in 16 (52 percent) it originated from the superficial femoral artery. Most musculocutaneous perforators of the saphenous artery were associated with the sartorius, whereas those of the descending genicular artery were associated with the vastus medialis. Superficial femoral artery skin perforators were noted in 10 thighs (32 percent). Two clinical cases, illustrating the use of the descending genicular artery vastus medialis perforator flap and of the distal-direct perforator osteocutaneous flap, are reported. CONCLUSIONS:: This study investigated the anatomical variations in the skin and bone perforators of the medial knee. Free skin or bone flaps were achieved in all specimens and osteocutaneous chimera flaps were achieved in 87 percent of the thighs. Copyright © 2013 by the American Society of Plastic Surgeons.